Experimental validation and development of an advanced computational model of a transcritical carbon dioxide vapour compression cycle with a thermoelectric subcooling system. (April 2022) - Casi, Álvaro; Aranguren, Patricia; Sanchez, Daniel; Araiz, Miguel; Cabello, Ramón; Astrain, David
Abstract: The inclusion of a thermoelectric subcooler as an alternative to increment the performance of a vapour compression cycle has been proved promising when properly designed and operated for low-medium power units. In this work, a computational model that simulates the behaviour of a carbon dioxide transcritical vapour compression cycle in conjunction with a thermoelectric subcooler system is presented. The computational tool is coded in Matlab and uses Refprop V9.1 to calculate the properties of the refrigerant at each point of the refrigeration cycle. Working conditions, effect of the heat exchangers of the subcooling system, temperature dependent thermoelectric properties, thermal contact resistances and the four thermoelectric effects are taken into account to increment its accuracy. The model has been validated using experimental data to prove the reliability and accuracy of the results obtained and shows deviations between the ± 7% for the most relevant outputs. Using the validated computational tool a 13.6 % COP improvement is predicted when optimizing the total number of thermoelectric modules of the subcooling system. The computational experimentally validated tool is properly fit to aid in the design and operation of thermoelectric subcooling systems, being able to predict the optimal configuration and operation settings for the whole refrigeration plant. Highlights: Transcritical CO2 vapour compression cycle with thermoelectric subcooling. Advanced computational model to predict optimal operation settings of the system. Validation of the model using experimental data with deviations between the ±7%. Computational optimization of the number of modules in a thermoelectric subcooler. 13.6% COP improvement using the hybrid solution and optimum number of modules.